DSP-Based Multi-Channel Spectral Shuffling Applied to Optical Networks - Abbade, Marcelo L. F. [UNESP]; Nogueira, Marcelo P. [UNESP]; Santos, Melissa O. [UNESP]; Fagotto, Eric A. M.; Bonani, Luiz H.; Aldaya, Ivan [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2020)
We propose a novel digital signal processing (DSP) technique that encrypts multiple baseband signals by dividing them into several spectral slices, which are then shuffled. Afterwards, the shuffled signals modulate optical carriers and are propagated through transparent optical communication systems. Simulation results reveal that the reach of shuffled signals is 90% of that of unshuffled ones. We also evaluate a scenario where the shuffled signals are transmitted through multiple routes to increase security and investigate the robustness of the technique against brute force and chosen plaintext attacks.
Keywords: digital signal processing; Network security; physical layer cryptography